Exploring the distinctive characteristics of gut microbiota across different horse breeds and ages using metataxonomics - Xinxi Qin; Li Xi; Longfei Zhao; Jincheng Han; Hongxia Qu; Yajun Xu; Weiping Weng (Frontiers in Cellular and Infection Microbiology)
BackgroundGut microbiota exerts a pivotal function in host nutrient metabolism and maturation of the mucosal immunity. Analyzing the reciprocal interaction between horses and gut microbiota constitutes a crucial aspect of scientific feeding practices. This study aims to investigate the differences in gut microbiota among Hequ horses, Mongolian horses, and Thoroughbred horses, as well as between Thoroughbred horses at two age stages.Methods and resultsPaired-end sequencing with a read length of 2×250 bp targeting the V3-V4 region of the 16S rRNA gene in fecal samples was carried out. Subsequently, differences in the diversity, composition, and metabolic pathways of the gut microbiota among the groups were analyzed. The results showed that: (1) Horse breeds were associated with variations in the gut microbiota. Microbial diversity, the proportion of commensal bacteria from Bacillota and Bacteroidota, and bacterial communities involved in dietary fiber metabolisms were significantly higher in the gut of the Hequ horses than in the gut of the Mongolian and Thoroughbred horses. The highest Bacillota to Bacteroidota (B/B) ratio and enrichment of bacterial communities involved in the metabolism of bile acids, lipids, and amino acids in the gut of the Mongolian horses resulted in significantly higher lipid metabolism and amino acid metabolism than in the other two breeds. The bacterial communities enriched in the gut of Thoroughbred horses were primarily involved in carbohydrate metabolism, but the level of energy metabolism was significantly lower than in Hequ horses. (2) The results also showed an association between age and gut microbiota of Thoroughbred horses. The alpha diversity, B/B ratio, and 83.33% of metabolic pathways did not differ significantly between younger and older Thoroughbred horses. However, there were significant differences between the two age groups in beta diversity, composition of glycolytic bacteria, metabolism of cofactors and vitamins, and energy metabolism of gut microbiota.ConclusionsCollectively, these results point to an association between the breed of horses or the age of Thoroughbred horses with variations in gut microbiota. The current findings will serve as a reference for improving feeding strategies for horses.